Behind the Iron Curtain: Sylvia Plath and Hungary during the Cold War - Dorka TAMÁS (E-REA)
This article looks at the under-researched topic broadly defined as Sylvia Plath’s relationship with Europe and European culture. Plath often highlighted that her European heritage was just as important to her as her American nationality. By focusing on Europe, I aim to shift the focus from Plath’s embeddedness in American culture and demonstrate that Plath was a multicultural and multifaceted writer and citizen. My research focuses on Plath’s relationship to one specific country, namely Hungary. While this at first may seem an odd choice, Sylvia Plath is tied in many ways to Hungary: she was courting with a Hungarian man and wrote about the 1956 Freedom Revolution against Russia. From her maternal side, she was also close geographically to Hungary, as her grandmother was from Austria. My essay reflects on the many ways Plath engaged with Hungary’s culture and politics as part of her broader interest in European culture and literature. On the other hand, while Plath experienced the Cold War context in the West, Hungary was part of the Iron Curtain of the East. There are parallels and opposition between Plath’s perception of the early stages of the Cold War and Hungary’s history. Plath’s novel The Bell Jar (1963) famously starts with the electrocution of the Rosenbergs; in Hungary, public places were named after the victims of the Cold War. I contextualise Plath’s knowledge and engagement with Hungary, which contributes to an inclusive reading of her writings, biography, and experiences of the early Cold War.